jAn Application of Function Sequences to the Darbo's Theorem with Integral Type Transformations - Karakaya, V; Sekman, D. (ISLAMIC AZAD UNIV, SHIRAZ BRANCH, 2020)
The purpose of this work is to investigate the behavior of function sequences under integral type transformations as a generalization of Darbo's theorem. It is also to obtain the existence of the fixed point of this transformation involving the function sequences. In addition, the study will be explained with an interesting example.
Keywords: Fixed point; integral type mapping; measure of noncompactness; function sequences; shifting distance function property; Mathematics